Urban development and poverty reduction – some institutional issues - Kwapong, T.F.O.A. (Journal of Information 1(1): 55 - 66, 2009)
It appears that the discussion on strategies to address poverty in rural and urban areas has been dominated by economists without adequate consideration of the difficult institutional issues that must be addressed for completeness. This paper focused on institutional issues confronting the urban sector. Specifically, three main objectives were achieved in this paper: (1)Provides a snapshot of the economic and social conditions of selected urban areas in Ghana; (2) Identifies some of the critical institutional issues confronting urban areas in Ghana, and (3) Suggests some policy directions that could be pursued to address the identified issues. The paper concludes that at the top of needed policy direction is political willingness and a genuine commitment to pro-poor policies which could be measured by the extent to which poor and vulnerable segments of the population in the urban areas are engaged in the process of visioning, planning, and implementing policies in support of urban development. In this process a horizontal integration between urban policy planners and adult education experts should be explored as a means to deepen stakeholders’ participation in poverty alleviation in the urban areas.
Keywords: Urban; poverty reduction; gender